Revising the Dynamic Loan Loss Provisioning System in Spain with Respect to the Recent Financial Crisis - Dobre, Roua Ioana (2012)
In this paper, the evolution of loan loss provisions in Spain is analysed, given the impact of the financial crisis on their levels and distinctiveness of the dynamic system used. The performance of such a unique provisioning system in a time of need is crucial to the assessment of its functionality. This, in turn, is important because it is a risk management system that keeps banks from going bankrupt, which as has been seen, can mean bankruptcy for the country of origin of the banks. Additionally, features inspired by this system are being incorporated in international accounting standards, so the impact of their functionality is global. In light of recent developments regarding the soundness of the financial system in Spain, the examination of the potential of dynamic provisioning to overcome the dangers faced by the banks nowadays becomes essential. Applying the Generalized Method of Moments estimator on a sample of 57 Spanish banks, I use empirical models to determine whether the income smoothing and pro-cyclicality theory change when dealing with dynamic provisions. The results show that income smoothing is still present, even though bank managers have been provided with a more transparent way to smooth their earnings. However, the dynamic provisions do have a counter-cyclical character, which helps the economy greatly. In conclusion, the dynamic provisioning system is a tool that works in the advantage of the banking sector and the country as a whole, provided it is used in conjunction with other helping mechanisms.